2017
DOI: 10.4103/ijccm.ijccm_279_17
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia in critically ill patients: Clinical and laboratorial behavior and its correlation with short-term outcome during hospitalization

Abstract: Background:Thrombocytopenia, being among the most common laboratory abnormality, found in Intensive Care Unit (ICU) patients is commonly associated with sepsis and disseminated intravascular coagulation. Declining platelet counts are associated with higher mortality rates. Thus, thrombocytopenia can be used as a prognostic marker in critically ill patients.Methodology:A prospective observational study was conducted on patients fulfilling the inclusion criteria and were evaluated for complete medical history, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 7 publications
3
47
0
Order By: Relevance
“…Platelet count is a simple and readily available biomarker, which is independently associated with disease severity and risk of mortality in the intensive care unit (ICU) [4][5][6]. Moreover, a low platelet count correlates with higher disease severity scores such as Multiple Organ Dysfunction Score (MODS), Simplified Acute Physiology Score (SAPS) II, and Acute Physiology and Chronic Health Evaluation (APACHE) II [5].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet count is a simple and readily available biomarker, which is independently associated with disease severity and risk of mortality in the intensive care unit (ICU) [4][5][6]. Moreover, a low platelet count correlates with higher disease severity scores such as Multiple Organ Dysfunction Score (MODS), Simplified Acute Physiology Score (SAPS) II, and Acute Physiology and Chronic Health Evaluation (APACHE) II [5].…”
Section: Introductionmentioning
confidence: 99%
“…The coagulopathy of sepsis is quite complex, composed of platelet dysfunction and abnormalities of the coagulation cascade. Thrombocytopenia, DIC, and decreased ADAMTS-13 activity have all been associated with poor outcomes in sepsis (31,33,34,44,45). We believe that coagulopathy is often present clinically, prior to laboratory derangements, so absolute values were not used to determine candidacy for treatment at our institution, or to monitor response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Lower plasma platelet level and high levels of PT, APTT, and D-dimer at admission are ominous for ROSC patients. Khurana et al [36] found that low platelet count and its progressive decline at admission indicated the severity of critically ill patients and were directly related to prognosis and mortality in ICU patients. Akca et al [37] studied 1,440 patients admitted to the ICU and showed that 30% of patients had a reduced platelet count at admission (PLT<150×10 9 /L), and the survivors had higher platelet counts.…”
Section: Discussionmentioning
confidence: 99%